In Vivo Role of Focal Adhesion Kinase in Regulating Pancreatic β-Cell Mass and Function Through Insulin Signaling, Actin Dynamics, and Granule Trafficking - Cai, Erica P. (American Diabetes Association, 2012)
Focal adhesion kinase (FAK) acts as an adaptor at the focal contacts serving as a junction between the extracellular matrix and actin cytoskeleton. Actin dynamics is known as a determinant step in insulin secretion. Additionally, FAK has been shown to regulate insulin signaling. To investigate the essential physiological role of FAK in pancreatic β-cells in vivo, we generated a transgenic mouse model using rat insulin promoter (RIP)–driven Cre-loxP recombination system to specifically delete FAK in pancreatic β-cells. These RIPcre(+)fak(fl/fl) mice exhibited glucose intolerance without changes in insulin sensitivity. Reduced β-cell viability and proliferation resulting in decreased β-cell mass was observed in these mice, which was associated with attenuated insulin/Akt (also known as protein kinase B) and extracellular signal–related kinase 1/2 signaling and increased caspase 3 activation. FAK-deficient β-cells exhibited impaired insulin secretion with normal glucose sensing and preserved Ca(2+) influx in response to glucose, but a reduced number of docked insulin granules and insulin exocytosis were found, which was associated with a decrease in focal proteins, paxillin and talin, and an impairment in actin depolymerization. This study is the first to show in vivo that FAK is critical for pancreatic β-cell viability and function through regulation in insulin signaling, actin dynamics, and granule trafficking.